On nonlocal purely critical and supercritical problems and superlinear semipositone problems - Kumar, Uttam (My University, 2022)
The main objective of this thesis is to examine purely critical and supercritical exponent problems involving nonlocal operator in the symmetric domain. The nonlocal superlinear semipositone problem is also investigated.
Tiwari, Sweta
Keywords: Nonlocal Problem; Critical and Supercritical Problem; Semipositone Problem